2022
DOI: 10.1002/cam4.5101
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced ultrasound (CEUS) of benign and malignant renal tumors: Distinguishing CEUS features differ with tumor size

Abstract: Background Contrast‐enhanced ultrasound (CEUS) is now a guideline‐recommended strategy for diagnosing renal lesions. Tumor size is related to the risk of the treatment and prognosis in renal tumors. Thus, we aim to analyze the CEUS features of solid renal tumors in relation to tumor size. Methods The CEUS appearance of 156 pathologically diagnosed solid renal tumors were retrospectively analyzed. Three groups were stratified according to the tumor size (≤2 cm [group I],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Subsequently, we compared and analyzed the differences in CUS and CEUS characteristics between benign and malignant tumors. Benign and malignant renal tumors in this study mostly presented as well-circumscribed round-like lesions, consistent with previous findings [17]. This may be related to the growth pattern of renal tumors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Subsequently, we compared and analyzed the differences in CUS and CEUS characteristics between benign and malignant tumors. Benign and malignant renal tumors in this study mostly presented as well-circumscribed round-like lesions, consistent with previous findings [17]. This may be related to the growth pattern of renal tumors.…”
Section: Discussionsupporting
confidence: 92%
“…As a low-cost and well-tolerated imaging method, CEUS can dynamically display microcirculatory perfusion and tumor vasculature in real time, and its value in differentiating between benign and malignant renal tumors has been widely recognized [16,17]. However, the specificity of CEUS in diagnosing benign and malignant renal tumors is relatively low due to the overlapping ultrasound findings across different pathological types, which cannot be judged solely from the contrast-enhanced mode [17]. In the CEUS mode, the hyperenhancement ring around the lesion can reflect the capillary condition in the pseudocapsule around the renal tumor with high specificity [8,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, multivariate Logistic regression analysis showed that the pseudocapsule sign is an independent predictor of RCC [ 16 ]. Zhu et al [ 17 ] reported a significant difference in the incidence of CEUS pseudocapsule visualization among RCC patients across various tumor-size subgroups. Notably, the highest pseudocapsule visualization rate was observed in medium-sized tumors (with a diameter of 2–4 cm), reaching 79.3%.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 27 ] suggested that the contrast-enhanced ultrasonographic findings of RCC may be affected by mass size. Jun Jiang [ 28 ] reported that there was no statistical significance between the peak intensity of CEUS of ccRCC and tumor size, but there was a good correlation between enhanced homogeneity and the frequency of pseudocapsule and tumor size.…”
Section: Discussionmentioning
confidence: 99%